2019
DOI: 10.1097/pec.0000000000001851
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Predictors of Using Opioids in the Emergency Department to Treat Migraine in Adolescents and Young Adults

Abstract: Objectives: This study aimed to determine the rate and context in which opioids are used to treat migraine in adolescents and young adults seen in emergency care settings.Methods: Data from 2010 to 2016 in the Cerner Health Facts electronic health record data warehouse were analyzed using multilevel logistic regression to estimate the population likelihood of an opioid being used in the emergency department (ED) to treat a primary diagnosis of migraine in adolescents and young adults and to evaluate the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Activation of these receptors decreases neurotransmitter release (pre-synaptic inhibition) and neuronal excitability (post-synaptic inhibition). There is some evidence that morphine produces greater analgesia in women and is more likely to be prescribed for women with migraine (Niesters et al, 2010;Connelly et al, 2019).…”
Section: Opioidsmentioning
confidence: 99%
“…Activation of these receptors decreases neurotransmitter release (pre-synaptic inhibition) and neuronal excitability (post-synaptic inhibition). There is some evidence that morphine produces greater analgesia in women and is more likely to be prescribed for women with migraine (Niesters et al, 2010;Connelly et al, 2019).…”
Section: Opioidsmentioning
confidence: 99%
“…1 In addition to variable efficacy of headache treatments received in the emergency department, 2,3 there are other limitations associated with this setting that can make it suboptimal for the acute management of migraine. Such limitations include a lack of headache-trained or informed providers, 4 -6 limited targeted interventions and comfort measures used for active headaches, 2,7,8 a higher rate of treatment with opioids, 9,10 and unnecessary imaging. 11,12 Developing alternative viable models for early therapeutic intervention of headaches may be advantageous to improve management and limit disability.…”
mentioning
confidence: 99%
“…6 Despite this, opioids are frequently prescribed for migraine across all ages and clinical settings. [7][8][9] One study found that opioids were administered in 35% of ED visits for headache, whereas triptans were administered in only 1.5% of visits. 10 Opioid use has also been shown to continue after the ED visit, with one study finding that approximately 20% of patients reported use of opioids at the time of presentation to a tertiary headache care center and ED physicians were among the most frequent first prescribers of the opioids.…”
Section: G U E S T E D I T O R I a Lmentioning
confidence: 99%